2012
DOI: 10.2166/nh.2012.057
|View full text |Cite
|
Sign up to set email alerts
|

Up-scaling surface runoff from plot to catchment scale

Abstract: The main aims of this study were to identify and characterize the flow processes at the plot scale, and to up-scale these processes at the catchment scaie by Terrain Analysis, using Digital Elevation Models (TauDEMs) based on in-situ sprinkling experiments. To calibrate the TauDEM-based method at the plot scale, in-situ sprinkling experiments were carried out on two plot scales (16 m^ divided into 16 plots of 1 m^ on various slopes). The marked differences in the textural and structural porosities between fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The higher porosity in green alder soil is due to the more intense root system of green alder that loosens the soil structure and promotes vertical infiltration (also limiting surface runoff generation). Similar results were found by Alaoui et al (2012) when grassland soil was compared to forest soil. The authors showed higher storage capacity in forest soil as compared to grassland soil, caused by the more intense root system having a significant effect on surface runoff (decrease).…”
Section: Characterization Of Grassland and Green Alder Soilssupporting
confidence: 85%
See 1 more Smart Citation
“…The higher porosity in green alder soil is due to the more intense root system of green alder that loosens the soil structure and promotes vertical infiltration (also limiting surface runoff generation). Similar results were found by Alaoui et al (2012) when grassland soil was compared to forest soil. The authors showed higher storage capacity in forest soil as compared to grassland soil, caused by the more intense root system having a significant effect on surface runoff (decrease).…”
Section: Characterization Of Grassland and Green Alder Soilssupporting
confidence: 85%
“…Similar results were found by Alaoui et al . () when grassland soil was compared to forest soil. The authors showed higher storage capacity in forest soil as compared to grassland soil, caused by the more intense root system having a significant effect on surface runoff (decrease). In Chämleten, the inverse phenomenon occurred (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of vegetation restoration on different kinds of soil erosion (i.e., river bank erosion and gully erosion) might be different. How to up-scale the soil erosion process to the larger scale is worth considering (Alaoui et al, 2012). Therefore, further studies should focus on analysing the effects of re-vegetation types on overland flow velocity, soil erosion control and surface water resource protection at different scales (i.e., landscape, hillslope, hydrologic response unit and patch).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are very useful in exploring hydrological processes (such as infiltration, overland flow, sediment transport and subsurface water flow) and local-level interactions among climate, soil, vegetation, topography and management practices [ 110 ]. However, plot-level parameters measured in situ cannot be expected to produce accurate predictions at all scales [ 111 ], and there are uncertainties when extrapolating findings from plot to catchment scales, or from small to large catchments [ 112 ]. The link between plot-scale and catchment-scale outcomes is critical for hydrological outcomes to be fully considered in landscape-level forest restoration planning.…”
Section: Essential Science Advancesmentioning
confidence: 99%